Use of the vertical electrical survey integrated to the chemical and microbiological analyzes in the preliminary diagnosis of soil and groundwater contamination in the rio claro city (SP) municipal cemetery - Xavier, Fernanda Vieira [UNESP]; Filho, Walter Malagutti [UNESP]; Silva, Robson Willians da Costa; Moreira, César Augusto [UNESP] (FapUNIFESP (SciELO), 2018)
Putrefative liquid is an effluent generated from the decomposition of bodies. In cemeteries, the leading cause of subsurface pollution is the liquefaction products percolation, which substantially alter the physical-chemical and biological characteristics of the soil. In Brazil, due to the lack of consistent planning due to cultural history, cemeteries are fully integrated into urban areas, which can be a public health problem. The risk of contamination is associated with the presence of elements such as nitrogen compounds, heavy metals, viruses and bacteria, with risks to human health. In the literature, these contaminants have been consistently identified in the geological environment through analytical results of water and soil compared to non affected areas. This research aimed to investigate possible changes in the subsurface physical environment of the Rio Claro city (São Paulo, Brazil) municipal cemetery, through the analytical results of the wells, supported by data obtained from the geophysical technique of vertical electrical sounding (VES). The results showed good correlation with the spatial and temporal evolution of the occupation of the cemetery throughout its history.
Emprego da sondagem elétrica vertical integrada às análises químicas e microbiológicas no diagnóstico preliminar da contaminação do solo e da água subterrânea no cemitério municipal da cidade de rio claro (SP)
Keywords: Contaminants; Electrical resistivity; Putrefative liquid